Therapeutic Potential of Seaweed-Derived Laminaran: Attenuation of Clinical Drug Cytotoxicity and Reactive Oxygen Species Scavenging - Hiromi Kurokawa; Thomas Kiran Marella; Hirofumi Matsui; Yutaka Kuroki; Makoto M. Watanabe (MDPI AG, 2023)
β-glucan has been shown to be effective for several diseases such as immune regulation and blood pressure suppression. Seaweed contains a β-1,3/1,6-glucan called laminaran. The present commercial source of β-glucan is black yeast; however, a fermentation process using organic carbon substrates makes production unsustainable, whereas macroalgae provide a sustainable alternative with the use of CO2 and seawater as growth substrates. However, bioactivity studies on laminaran are limited. We aimed to evaluate whether laminaran can scavenge reactive oxygen species (ROS) and attenuate cytotoxicity caused by clinical drugs such as indomethacin (Ind) and dabigatran (Dab). Electron spin resonance assay revealed that laminaran scavenged singlet oxygen (1O2) and superoxide anions (O2•−) directly but did not scavenge hydroxyl radicals (•OH). Mitochondrial ROS detection dye showed that laminaran scavenged mitochondrial O2•− produced upon administration of Ind or Dab. Moreover, significant reductions in •OH and peroxynitrate (ONOO−) levels were observed. Since •OH and ONOO− are generated from O2•− in the cells, laminaran could indirectly suppress the generation of •OH and ONOO− via the removal of O2•−. Both Ind and Dab induce cell injury via ROS production. Laminaran attenuated the cytotoxicity derived from these drugs and may represent a functional food with anti-aging and disease prevention properties.